The Relationship between the Cryptocurrency Value (Bitcoin) and Interest for it in the Region - Kristian Dokic; Mirjana Radman Funaric; Katarina Potnik Galic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Recently the term Cryptocurrency is a frequently used in the mainstream media. The main reason for that is a bitcoin occurrence with reference to the technology and cryptographic inventions that stand behind the bitcoin. Cryptocurrency is legal in region because the European Union has liberal monetary regulations and it can be seen that region successfully follows the world trends in this field. The goal of this paper is to indicate a strong relationship between the value of Bitcoin and expressed interest for it in 11 South-East Europe region countries. The last four and half years will be analysed on a monthly base and data from service Google Trends will be used. Spearman's rank correlation between the expressed interest and bitcoin values for the last four and half years will be calculated. Comment on strong relationship between those variables will be given at the end.
Keywords: E42; 330; cryptocurrency; bitcoin; ICT